NaOH Concentration-Dependent Silanol Formation and Pb2+ Adsorption by Waste Glass-Derived Silica Gel - Renanda Ridela; Putri Monika, Dea; Khair, Miftahul (Jurnal Pendidikan Tambusai, 2024)
Clear glass waste, a prevalent inorganic waste in Indonesia, presents an opportunity for eco-friendly adsorbent development. This study explored the impact of varying NaOH concentrations (1M-4M) on the Pb2+ ion adsorption capacity of silica gel synthesized from clear glass waste via the sol-gel method.While conclusive determination of the optimal NaOH concentration for Pb2+ adsorption remained outside the study's scope, valuable insights were obtained. FTIR analysis confirmed the presence of silanol (SiOH) and siloxane (Si-O-Si) groups within the silica gel structure, with the SiOH group specifically identified at a wavenumber of 957 cm?¹. Increasing NaOH concentration from 0.5 M to 4 M significantly enhanced the formation of silanol groups on the silica gel surface, as evidenced by the increasing area of the corresponding peak in the FTIR spectrum (3.2 to 71.0 arbitrary units). This positive influence translated to an improved Pb2+ adsorption capacity, with the highest performance of 2.3 mg/g achieved at the highest NaOH concentration. However, the relationship wasn't perfectly linear, suggesting the influence of additional factors like silanol distribution and the presence of competing ions. This work demonstrates the potential of waste glass-derived silica gel for Pb2+ remediation while emphasizing the need for further research to optimize synthesis parameters and elucidate the full adsorption mechanisms.